Novel, anatomically appropriate balloon dilation technique of the glottis to treat posterior glottic stenosis in a 3D‐printed model. (18th February 2019) - Cates, Daniel J.; Magnetta, Michael J.; Smith, Libby J.; Rosen, Clark A.
Abstract : Objective: Posterior glottic stenosis (PGS) often requires a destructive surgical treatment. Early PGS treatment involves glottic dilation to reduce airway constriction associated with chronic PGS. Round laryngeal dilation may not optimize posterior glottic dilation due to the teardrop shape of the glottis and may injure vocal fold tissue. We compared pressure applied to the glottis during traditional single balloon dilation and a novel, anatomically appropriate dilation technique (teardrop‐shaped glottic dilation [TSGD]). Methods: Pressure sensors were affixed at various points on a three‐dimensional printed glottic model. The anterior glottis was stented with a triangular stent (18‐32F) in combination with balloon dilator (10–20 mm) placed in the posterior glottis (TSGD) in 30 unique combinations. Force applied to the vocal folds (VF) and posterior commissure (PC) during round balloon dilation and TSGD was measured. Results: Dilatory force in the PC ranged from 0.0–3.8 newtons (N) using balloon dilators and 0.0–17.5 N using TSGD. The TSGD technique yielded a superior ratio of force applied to the PC versus VF ( P = 0.0296) compared to round balloon dilation alone. Optimal targeting of the PC occurred when the sum of the anteroposterior (AP) dimensions of the stent and balloon dilator approached the AP length of the glottis. Conclusion: Use of an anatomically appropriate glottic dilation maximizes expansive force applied to the posterior commissure and decreased force to the vocal folds. This study demonstrates that TSGD minimizes force to the anterior glottis and maximizes dilation of the posterior glottis. This technique may play a role in preventing laryngeal stenosis associated with chronic PGS. Level of Evidence: NA Laryngoscope, 129:2239–2243, 2019